Thermodynamic and kinetic studies on novel dinuclear platinum(II) complexes containing bidentate N, N -donor ligands - Hochreuther, Stephanie; Puchta, Ralph; van Eldik, Rudi (Inorganic Chemistry, 2011)
A series of novel dinuclear platinum(II) complexes were synthesized with bidentate nitrogen donor ligands. The two platinum centers are connected by an aliphatic chain of variable length. The selected chelating ligand system should stabilize the complex toward decomposition. The pKa values and reactivity of four synthesized complexes, viz. [Pt2(N 1,N4-bis(2-pyridylmethyl)-1,4-butanediamine)(OH 2)4]4+ (4NNpy), [Pt2(N 1,N6-bis(2-pyridylmethyl)-1,6-hexanediamine)(OH 2)4]4+ (6NNpy), [Pt2(N 1,N8-bis(2-pyridylmethyl)-1,8-octanediamine)(OH 2)4]4+ (8NNpy), and [Pt2(N 1,N10-bis(2-pyridylmethyl)-1,10-decanediamine)(OH 2)4]4+ (10NNpy), were investigated. This system is of special interest because only little is known about the substitution behavior of dinuclear platinum complexes that contain a bidentate chelate that forms part of the aliphatic bridging ligand. Spectrophotometric acid-base titrations were performed to determine the pKa values of the coordinated water ligands. The substitution of coordinated water by thiourea was studied under pseudofirst-order conditions as a function of nucleophile concentration, temperature, and pressure, using stopped-flow techniques and UV-vis spectroscopy. The results for the dinuclear complexes were compared to those for the corresponding mononuclear reference complex [Pt(aminomethylpyridine)(OH2)2]2+ (monoNNpy), by which the effect of increasing the aliphatic chain length on the bridged complexes could be investigated. The results indicated that there is a clear interaction between the two platinum centers, which becomes weaker as the chain length between the metal centers increases. In addition, quantum chemical calculations were performed to support the interpretation and discussion of the experimental data. © 2011 American Chemical Society.
CRIS-Team Scopus Importer:2026-01-22